Study guide to accompany Basic engineering circuit analysis - Dillard, Bill. (J. Wiley, 1999)
Basic concepts. Resistive circuits. Nodal & loop analysis techniques. Additional analysis techniques. Capacitance & inductance. First-order transient circuits. Second-order transient circuits. AC steady-state analysis...